Finite element simulation of daily activities held by the intervertebral disc - Correia, Hélder Tiago Vieira (2013)
The spine is a complex system, capable of maintaining stability and simultaneously performing movements and the lumbar region is fundamental for this ability. The present work aims to validate a Finite Elements (FE) model of a lumbar motion segment, through numerical simulation of the required mobility on the intervertebral disc, accordingly to some daily activities. For this study, only the simplest motion on the spine was simulated: flexion, extension and lateral bending. The biomechanical response of the FE model has proved to be suitable for predictions on flexion, but on extension and lateral flexion unexpected extension angles were obtained. These results showed the need of improvements in the mesh geometry, along with the introduction of a model considering of the external ligaments restraining effect, in order to get a more reliable and closer to reality simulation of the all biomechanical system.